Management of malignant colorectal polyps in New Zealand. Issue 5 (8th April 2016) - Fischer, Jesse; Dobbs, Bruce; Dixon, Liane; Eglinton, Tim W.; Wakeman, Christopher J.; Frizelle, Frank A.
Abstract : Background: The management of colorectal polyps containing a focus of malignancy is problematic, and the risks of under‐ and over‐treatment must be balanced. The primary aim of this study was to describe the management and outcomes of patients with malignant polyps in the New Zealand population; the secondary aim was to investigate prognostic factors. Methods: Retrospective review of relevant clinical records at five New Zealand District Health Boards. Results: Out of the 414 patients identified, 51 patients were excluded because of the presence of other relevant colorectal pathology, leaving 363 patients for analysis. Of these, 182 had a polypectomy, and 181 had a bowel resection as definitive treatment. The overall 5‐year survival was not altered with resection but was improved with re‐excision of any form (repeat polypectomy or bowel resection). There were 110 rectal lesions and 253 colonic lesions. A total of 16% of patients who had resection after polypectomy were found to have residual cancer in the resected specimen. Ischaemic heart disease, chronic obstructive pulmonary disease and metastatic disease were found to negatively impact overall survival ( P < 0.001). Resection was more likely to follow polypectomy if polypectomy margins were positive, fragmentation occurred for sessile lesions and for pedunculated lesions with a higher Haggitt level. Conclusion: Polypectomy is oncologically safe in selected patients. Re‐excision improves overall survival and should be considered in patients with low comorbidity (American Society of Anesthesiologists score 1 and 2) and where there is concern about margins (sessile lesions and positive polypectomy margins). In the majority of patients, however, no residual disease is found.